'Pierre Menard, autor del Quijote' and the Death of Borges's Father. (3rd July 2021) - Williamson, Edwin
ABSTRACT: The young Borges sought to forge a literary destiny of his own, freed from his family's expectation that he compensate for the literary destiny that had been denied his father, but it was the failure of that endeavour that resulted in the kind of work that actually made his name. Far from being the product of a frigid, cerebral writer enclosed in a literary utopia, Borges's early ficciones were generated by a complex ordeal originating in his relationship with a young woman in the 1920s and eventually brought to a head by his dying father's request that his son 're-write' his novel El caudillo . Pivotal in this process was 'Pierre Menard, autor del Quijote ' because, in this ingenious text, Borges at last found a way of transforming abstract ideas into figurative vehicles for his own desolation and angst. From this discovery would spring the philosophical themes that would enable him to articulate profound existential concerns in his ficciones — the elusiveness of reality, the evanescence of the self, solipsism, the mysteries of time, and the horror of the infinite.